KOMPETENSI KADER DALAM PENCEGAHAN STUNTING DI PUSKESMAS POLOWIJEN KOTA MALANG - Dian Hanifah; Lilik Winarsih (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2021)
Reducing the stunting rate to 40% by 2025 will be the second target of the Sustainable Development Goal’s (SD' G’s). One of the government programs in reducing the stunting prevalence is the Healthy Indonesia Program with a Family Approach. Cadre means the volunteers formed by the community who are concerned about improving the health quality of the surrounding environment. Cadres are expected to have competence in understanding the contents of the KIA book. Moreover, they must be able to detect stunting by measuring the child's height/length and weight correctly. The purpose of this study was to analyze the strengthening of cadres' competence in preventing stunting through the use of the KIA book. This research is experimental research with a quantitative approach by using the one-group pretest and posttest design. This research was conducted from July to September 2020 at Polowijen medical center of Malang. Data collection used questionnaires and checklists. The treatment of respondents used training learning methods. The population in this study were cadres from the maternal & child health center at Polowijen medical center area. The number of samples in this study was 51 respondents. Based on the research conducted, the results showed that the competence of cadres before treatment was a mean of 66.39, a median of 31 with 82 of the maximum score, and 51 of the minimum score. The data after treatment obtained a mean of 66.37, a median of 27 with the 80 of the maximum score, and 53 of the minimum score. The results of the correlation test showed the closeness of the relationship between before and after the cadres studied the KIA book (the correlation value was 0.54 and it was obtained for the P-value (0.000) <α (0.05).